Análise do desempenho econômico-financeiro de seguradoras - Fabricia de Farias da Silva (2008)
This research analyzes the performance of Brazilian insurance companies in the period between 2000 and 2006, using Data Envelopment Analysis (DEA) as tool to find the most efficient companies in each studied period and in one general ranking of all periods. Theliterature review encompasses the history and development of the insurance market, as well as the main specific characteristics of this sector. The research was of a descriptive nature and was based on quantitative and qualitative analysis. The quantitative analysis was based on the DEA technique and aimed at finding the most efficient insurance companies. The development of the DEA model required statistical analyses to select the variables that would compose the model. The qualitative part of the research was based on four case studies ofinsurance companies operating in the Brazilian market. The qualitative analysis aimed at identifying the way these companies analyze both their financial and operational performance. It was possible to find the most efficient companies in each studied year, according to the statistical and DEA analysis. These companies can be considered as reference to the analysis of all the companies in the market. Moreover, it was possible do develop a ranking of the efficiency of the insurance companies. This ranking is based on the economic and financial performance of the companies presented during the years considered in the analysis. One ofthe main conclusions from the case studies was that the insurance companies carry their performance evaluation with the basis on both financial ratios and non-financial ratios.